2023
DOI: 10.1021/acsbiomaterials.3c00059
|View full text |Cite
|
Sign up to set email alerts
|

Bilayer Silk Fibroin/Sodium Alginate Scaffold Delivered hUC-MSCs to Enhance Skin Scarless Healing and Hair Follicle Regeneration with the IRE1/XBP1 Pathway Inhibition

Abstract: Efficient local delivery of mesenchymal stem cells (MSCs) is a decisive factor for their application in regeneration processes. Here, we prepared a biomimetic bilayer silk fibroin/sodium alginate (SF/SA) scaffold to deliver human umbilical mesenchymal stem cells (hUC-MSCs) for wound healing. An SA membrane was prepared by the casting method on the upper layer of the scaffold to simulate the dense epidermal structure. On the lower layer, porous materials simulating the loose structure of the dermis were formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Mesenchymal stem cells (MSCs) are a type of multipotent stem cells that possess differentiation abilities, immunomodulatory effects, and homing properties. They are considered one of the most promising biological agents for enhancing tissue regenerative capacity. Multiple experiments have indicated that MSCs play a vital role in neovascularization of ischemic tissues, including wound healing, , ischemia of the hind limb, and myocardial infarction . Cell-based therapies utilizing MSCs can also be employed as an effective method to regulate vascularization and immune responses through the secretion of growth factors, cytokines and exosomes, ultimately improving skin flap survival and functional recovery. , However, the failure of most clinical stage MSC therapies suggests that the inherent therapeutic benefits of MSCs when administered to humans are not as vigorous as demonstrated in preclinical studies .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesenchymal stem cells (MSCs) are a type of multipotent stem cells that possess differentiation abilities, immunomodulatory effects, and homing properties. They are considered one of the most promising biological agents for enhancing tissue regenerative capacity. Multiple experiments have indicated that MSCs play a vital role in neovascularization of ischemic tissues, including wound healing, , ischemia of the hind limb, and myocardial infarction . Cell-based therapies utilizing MSCs can also be employed as an effective method to regulate vascularization and immune responses through the secretion of growth factors, cytokines and exosomes, ultimately improving skin flap survival and functional recovery. , However, the failure of most clinical stage MSC therapies suggests that the inherent therapeutic benefits of MSCs when administered to humans are not as vigorous as demonstrated in preclinical studies .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the transplantation of cells with biomaterial scaffolds has emerged as a promising strategy for cell-based therapies , due to the scaffolds’ ability to prolong cell retention, providing appropriate cellular niches for the implanted cells and guide tissue regrowth. ,, The synergistic roles of MSCs and hydrogel scaffolds in skin flap regeneration have also been demonstrated. , However, the significant level reactive oxygen species (ROS) and inflammatory response in the injured tissue were ignored, which not only jeopardized cell proliferation and functions but also triggered apoptosis, , ultimately impeding tissue regeneration. Therefore, it is critical to regulate the harsh microenvironment and promote cell viability to ensure the survival of MSCs following implantation and regeneration of damaged tissue.…”
Section: Introductionmentioning
confidence: 99%